Bridging the GAAP? : IFRS in accounting practice - Hartmann, Berit (Jönköping International Business School, 2013)
This thesis investigates how International Financial Reporting Standards (IFRS) come to act within an organizational context. In particular, the thesis explores how the requirements for goodwill accounting and leasing influence organizational calculative practices, transforming and shaping operations management. Drawing on actor-network theory, this study moves away from a priori distinctions, following the construction and mobilization of accounting numbers across institutionalized boundaries within and around the organization. The empirical investigation took place in a large, worldwide active media group that is listed on a European stock exchange. The group is a particular interesting setting because of its diverse business structure and its German code-law accounting roots. Business combinations are a major growth factor within the industry and a high degree of decentralization in the organization placed responsibility for investment decisions at low hierarchical levels. Goodwill accounting and impairment testing were therefore highly significant calculative practices in the group. The study finds that the constitutive role of the financial reporting standards in the organization both solves tensions and dilemmas around the number and creates new ones when crucial interests are lost in translation. These tensions and dilemmas arise between the aim of standardization and closure for the construction of a legitimate value of the future, and the aim to mobilize numbers in order to motivate and create value for a future. Originally intended for the financial representation of organizational substance and performance, the standards become associated with operations management activities, helping to create the faithful records that sum up the organization. This interrelation helps to close concern around the representation of the future in a ‘fair’ value by distributing the calculative practices over a wide network of actors spanning inside and outside the organization. However, the relationship also forces a connection between calculations and ambitions that otherwise would have preferred to stay separate. This thesis offers a new perspective on IFRS implementation by emphasizing organizational activities. Through a focus on integration and the link between financial and management accounting, the ‘implementation problems’ highlighted in previous literature gain a refined theorization. When taking organizational practice seriously, integration becomes a process that may find temporal stability but will never be final. In the process, conflicts might be solved but new dilemmas will arise. In turn, concepts like decision usefulness, comparability and earnings management cannot exist in a stable form but are rather constructed in networks that disregard commonly assumed boundaries inside and around the organization.
Keywords: IFRS; International Financial Reporting Standards